2014
DOI: 10.1186/1471-227x-14-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for delayed encephalopathy following acute carbon monoxide poisoning

Abstract: BackgroundIn Japan, many carbon monoxide (CO) poisoning cases are transported to emergency settings, making treatment and prognostic assessment an urgent task. However, there is currently no reliable means to predict whether “delayed neuropsychiatric sequelae (DNS)” will develop after acute CO poisoning. This study is intended to find out risk factors for the development of DNS and to characterize the clinical course following the development of DNS in acute CO poisoning cases.MethodsThis is a retrospective co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
33
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 17 publications
(19 reference statements)
8
33
1
2
Order By: Relevance
“…We identified the following prognostic factors associated with DNS development in patients with severe CO poisoning: LOC, lower GCS score, GCS score of 3, intubation requirement, elevated Tn level, and higher levels of Tn and CK. Other investigational prognostic markers reported worldwide include S100B protein, 24 low Mini-Mental State Examination score, 25 positive computed tomography of brain, 25,26 and plasma copeptin. 27 The results of this study reveal that severe DNS did not develop in any patient with severe CO poisoning who was treated with HBOT at PYNEH between 2008 and 2013.…”
Section: Pathophysiology Of Carbon Monoxide Poisoningmentioning
confidence: 99%
“…We identified the following prognostic factors associated with DNS development in patients with severe CO poisoning: LOC, lower GCS score, GCS score of 3, intubation requirement, elevated Tn level, and higher levels of Tn and CK. Other investigational prognostic markers reported worldwide include S100B protein, 24 low Mini-Mental State Examination score, 25 positive computed tomography of brain, 25,26 and plasma copeptin. 27 The results of this study reveal that severe DNS did not develop in any patient with severe CO poisoning who was treated with HBOT at PYNEH between 2008 and 2013.…”
Section: Pathophysiology Of Carbon Monoxide Poisoningmentioning
confidence: 99%
“…Pepe et al reported that 24.1% incidence of DNS at 30 days from hospital discharge [5]. The risk factors that have been associated with the development of DNS include advanced age group, longer duration of exposure to carbon monoxide, delayed time in seeking treatment, duration of loss of consciousness, coma, early changes on head computed tomography (CT) or magnetic resonance (MRI) and grossly elevated CK, CKMB and LDH levels on blood investigations and severe metabolic acidosis [3,5,[8][9][10][11]. In this patient, the risk factors to develop DNS were prolonged exposure to carbon monoxide, presented in coma and had severe metabolic acidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous associated diseases do not hasten the development of sequelae [7,8,9]. Possible prognostic factors for the development of DNS in patients with severe CO poisoning are serious disorders of consciousness or loss of consciousness at emergency admission, low Glasgow Coma Scale (GCS) score, head CT findings indicating hypoxic encephalopathy, haematology findings including high troponin, creatine phosphokinase, creatine kinase-MB and lactate dehydrogenase levels, low Global Assessment Scale scores, and intubation requirement [22,23]. Other factors that may be associated with increased risk of DNS development are: CO exposure duration >6 hours, GCS score <9, seizures, systolic blood pressure <90 mmHg and leukocytosis, but in the multivariate analysis the independent factors were only the GCS <9 (OR 7.15; CI 95%: 1.04-48.8) and leukocytosis (OR 3.31; CI 95%: 1.02-10.71) [24].…”
Section: Discussionmentioning
confidence: 99%